Determinasi Profitabilitas Perusahaan: Analisis Pengaruh Pertumbuhan Penjualan, Leverage, Dan Ukuran Perusahaan Pada Sektor Consumer Non Cyclical - Napitupulu, Meris; Herninta, Tiwi (Media Ilmiah Akuntansi, 2025)
This study aims to analyze the influence of sales growth, leverage, and firm size on corporate profitability in the Consumer Non Cyclicals sector listed on the Indonesia Stock Exchange (BEI) during the period 2019–2023. The method used was associative research with a quantitative approach. Purposive sampling was applied to select 34 companies, resulting in 170 observations. Data analysis utilized descriptive statistics and panel data regression. The result of the simultaneous test (F-test) indicates that the independent variables collectively and significantly influence profitability. However, partially, the results show that Sales Growth does not have a significant influence on Profitability (Prob. 0.6197). Conversely, Leverage has a significant negative influence on Profitability (Prob. 0.0001). Furthermore, Firm Size has a significant positive influence on Profitability (Prob. 0.0038). High leverage leads to higher interest burdens, which reduces profit. Large firms (high total assets) are often able to enhance productivity and revenue, thereby increasing profitability.